OPTIMIZATION OF HOUSEHOLD PLASTIC WASTE MANAGEMENT THROUGH THE DEVELOPMENT OF AN INNOVATIVE WASTE BANK BASED ON LEGAL AND K3 EDUCATION - Nely Tangke Rante; Chingta Dewi Stanley; Lukas Salempang (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Household plastic waste management is a critical environmental issue that requires a comprehensive behaviour-based approach. This study aims to analyze the effectiveness of an integrated intervention model optimizing household plastic waste management in RT 34, Manggar Subdistrict, East Balikpapan. The program was designed using the Theory of Planned Behaviour (TPB) framework and implemented through a Participatory Action Research (PAR) approach with a quasi-experimental one-group pre-test/post-test design. The intervention consisted of three main components: the provision of innovative two-compartment trash bins, the establishment and operationalization of a waste bank system, and legal and Occupational Health and Safety (OHS) education. The study involved 85 households as research participants. Quantitative data were collected using Likert-scale questionnaires measuring attitudes, subjective norms, perceived behavioural control, and behavioural intentions, and were analysed using a paired-samples t-test. Secondary data were obtained from waste bank operational records, while qualitative data were analyzed thematically through observation and focus group discussions. The findings indicate statistically significant improvements across all TPB constructs following the intervention. Active community participation reached 88%, with managed plastic waste volume increasing to two-thirds of the bin capacity per month. These results demonstrate that the synergy of physical, institutional, and educational interventions effectively strengthens behavioural intentions and translates them into sustainable waste management practices. This model has strong potential to be replicated in other urban community empowerment initiatives based on circular economic principles.